On numerical simulation of airfoil vibrations induced by compressible flow - Feistauer, Miloslav; Česenek, Jan (Proceedings of the Conference Algoritmy, 2015)
The subject of the paper is the numerical simulation of the interaction of two-dimensional compressible viscous °ow and a vibrating airfoil. The airfoil is considered as a solid body with two degrees of freedom, moving in the vertical direction and rotating around an elastic axis. The numerical simulation consists of the solution of the Navier-Stokes system by the space discontinuous Galerkin method combined with BDF in time, coupled with a system of nonlinear ordinary differential equations describing the airfoil motion. The time-dependent computational domain and a moving grid are taken into account by the arbitrary Lagrangian-Eulerian (ALE) formulation of the Navier-Stokes equations. The applicability of the developed method is demonstrated by numerical experiments.